2020
DOI: 10.3390/nu12071907
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Are Associated with Risk of Prostate Cancer in a Population-Based Case-Control Study in Montreal, Canada

Abstract: This study describes the association between dietary patterns and prostate cancer (PCa) risk in a population-based case-control study conducted in Montreal, Canada (2005–2012). Cases (n = 1919) were histologically confirmed, aged ≤75 years. Concomitantly, controls (n = 1991) were randomly selected from the electoral list and frequency-matched to cases by age (±5 years). During face-to-face interviews, a 63-item food frequency questionnaire focusing on the two years before diagnosis/interview was administered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 42 publications
(88 reference statements)
4
22
1
Order By: Relevance
“…However, comparison with previous studies is very complex, given that: (i) dietary patterns were constructed a posteriori, and, therefore, are dependent on the study population; and (ii) the food and beverage groups included differed between studies. Considering these limitations, our findings are in line with two case-control studies [ 21 , 24 ]. Trudeau et al, in a case-control study carried out in Canada, identified a pattern called “Sweets and Beverages”, characterized by high intakes of pasta, pizza, cookies, chips, chocolate, and carbonated soft drinks, which was associated with increased odds of PCa (OR Q4vsQ1 = 1.35 (95% CI 1.10–1.66)) [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, comparison with previous studies is very complex, given that: (i) dietary patterns were constructed a posteriori, and, therefore, are dependent on the study population; and (ii) the food and beverage groups included differed between studies. Considering these limitations, our findings are in line with two case-control studies [ 21 , 24 ]. Trudeau et al, in a case-control study carried out in Canada, identified a pattern called “Sweets and Beverages”, characterized by high intakes of pasta, pizza, cookies, chips, chocolate, and carbonated soft drinks, which was associated with increased odds of PCa (OR Q4vsQ1 = 1.35 (95% CI 1.10–1.66)) [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…Within the a posteriori approaches, principal component analysis is the most used method [ 17 , 19 , 20 ]. Using this method, multiple dietary patterns have been identified, such as Western or Traditional, Mediterranean, prudent patterns named according to the foods or food groups consumed [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Thus, adherence to a Western or Traditional pattern has been associated with increased risk of PCa [ 25 , 26 , 27 , 29 ], while adherence to a healthy or Mediterranean pattern has been associated with lower risk of PCa [ 21 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature on nutrition, the typical range is 20% to 30% of the total variance explained by two or three dietary factors (dietary patterns). In this light, the current result (31% for three factors) is better than many previously reported [ 86 , 87 , 88 , 89 ]. The strength of a statistical analysis is the sample size—sufficient for PCA performance (the subject-to-item ratio 19:1) [ 61 ].…”
Section: Discussioncontrasting
confidence: 81%